KLITIKS BERMAKNA NUMERIK DALAM BAHASA INDONESIA - Kabul Prasetya (ASMARALOKA : Jurnal Bidang Pendidikan, Linguistik dan Sastra Indonesia, 2025)
This study examines bound morphemes with numerical meanings in the Indonesian language, focusing on how the language accommodates numerical and quantitative concepts in forming efficient vocabulary. The main challenge lies in finding an appropriate mechanism to convey stable numerical meanings without altering the fundamental structure or word classes. However, the mechanisms by which numerical morphemes are used remain poorly understood, particularly in terms of their semantic stability and contribution to technology- and culture-based vocabulary. This research employs a qualitative descriptive method to explore the functions and structures of numerical morphemes such as bi- (two), tri- (three), and panca- (five) within the morphological context of the Indonesian language. Data were sourced from the Kamus Besar Bahasa Indonesia (KBBI). The findings reveal that bound numerical morphemes play a significant role in conveying quantitative information and serve as a tool for lexical development without altering the base word's class. Additionally, prefixes such as mega- and giga- enable Indonesian to align with internationally common terminology in scientific domains while retaining its agglutinative nature. These bound numerical morphemes offer an effective and flexible linguistic mechanism to support vocabulary development relevant to modern communication needs, balancing global integration with cultural identity preservation.